The relationship between obesity, hemoglobin A1c and the severity of COVID-19 at an urban tertiary care center in New York City: a retrospective cohort study. Issue 1 (31st January 2021) - Randhawa, Gurchetan; Syed, Kunzah A; Singh, Kavish; Kundal, Sanchit V; Oli, Sharad; Silver, Michael; Syed, Sumrah A; Suban Na Ayutthaya, Thanunthorn; Williams, Shanado; Lodato, Zachary L; Rozvadovskiy, Vladimir; Kamholz, Stephan; et al.
Abstract : Objectives: To determine if obesity and diabetes are risk factors for severe outcomes in COVID-19 and to compare patient outcomes in those two conditions. Design: Retrospective cohort study. Setting: Urban tertiary care center in New York City. Participants: 302 patients admitted in an inpatient setting, ≥18 years old, with a laboratory-confirmed diagnosis of COVID-19 via nasal PCR swab were randomly selected. Patients were separated into two cohorts based on their body mass index and hemoglobin A1c. 150 patients were placed in the non-obese, non-diabetic cohort and 152 patients were placed in the corresponding cohort (obesity alone, obesity and diabetes, and diabetes alone). Measurements: Primary outcomes were development of acute kidney injury, commencement of renal replacement therapy, aminotransferase elevation, troponin elevation, lactic acidosis, development of septic shock, use of vasopressors, presence of acute respiratory distress syndrome (ARDS) and intubation. The secondary outcomes were length of stay in days and mortality. Results: Patients with obesity and/or diabetes were more likely to develop ARDS (79 patients vs 57 patients, p<0.0001) and to be intubated (71 patients vs 45 patients, p=0.0031). Patients with obesity and/or diabetes were more likely to require vasopressors (60 patients vs 41 patients, p=0.0284) and to develop lactic acidosis (median 3.15 mmol/L, IQR 1.8 to 5.2 mmol/L, p=0.0432). When comparing patients with diabetes with and without obesity against patients with obesity alone, they were more likely to develop ARDS (87.5%, p=0.0305). Despite these findings, there was no difference in mortality. Conclusions: In patients hospitalised with COVID-19, those with obesity and/or diabetes were more likely to suffer severe complications, but had negligible differences in mortality. This highlights the importance of close monitoring of patients with these conditions and additional areas of research needed to explain the mortality findings.